Value Engineering in Enhancing Green Building Innovation - Kumara, I Nyoman Indra; Tapa, I Gede Fery Surya; Indrashwara, Decky Cipta; Pancane, I Wayan Dikse; Predana, Made Aryatirta (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
This research integrates the application of value engineering methods in buildings to enhance green building innovation. The use of value engineering methods, assisted by Dell'Isola Theory, functions as a structured framework to determine material substitution and streamline project value by considering quality, performance, cost, development sustainability, and energy efficiency. Through careful analysis and strategic application, this research presents innovations in improving cost efficiency and development sustainability in building construction projects. These findings indicate the potential for innovation in creating environmentally friendly yet economically viable environments. Furthermore, it can also contribute to reducing environmental impacts and supporting sustainable development goals.